2020
DOI: 10.3390/molecules25184114
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of Juniperus communis L. Berry Ethanol Extracts: 1. In Vitro Hydroxyl Radical Scavenging Activity

Abstract: In the present study, in vitro hydroxyl radical scavenging activities, total phenols and terpene contents in 70% ethanol extracts were evaluated. Samples of crushed (CB) and non-crushed ripe juniper berries (NCB) collected at five localities in North-East Slovakia during the years 2012–2014 were compared. Standard or modified methods for determining phytochemical and antioxidant activity were used together with a novel method for the evaluation of the results after the correction of the measured values per gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…Total terpenoids ranged from 23 to 133 mg/g DE for JB1 extracts and from 17 to 110 mg/g DE for JB2 extracts. Fejér et al reported that the total terpenoids in 70% ethanol extract ranged from 38 to 80 mg/g DE, which is comparable to our research data [25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Total terpenoids ranged from 23 to 133 mg/g DE for JB1 extracts and from 17 to 110 mg/g DE for JB2 extracts. Fejér et al reported that the total terpenoids in 70% ethanol extract ranged from 38 to 80 mg/g DE, which is comparable to our research data [25].…”
Section: Discussionsupporting
confidence: 92%
“…The total content of phenolic compounds for JB1 extracts ranged from 1.12 to 56.15 mg equivalent of gallic acid (GAE) per g dry extract; for JB2 extracts, this ranged from 0.93 to 11.1 mg equivalent of gallic acid (GAE) per g dry extract. These data were lower than in the other described works; the total phenolic content for JB2 extracts of J. communis from different origins, such as Turkey, Slovakia, Canada, Australia, Portugal, and Romania, varied in the range of 0.19-99 mg equivalent of gallic acid (GAE) per g dry extract (dw) [10,25,31,[34][35][36]. Orhan et al reported that the total phenolic content of JB1 was 130.92 mg equivalent of gallic acid (GAE) per g dry extract [37].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The • OH and • DPPH radicals are an extremely active free radical in biological systems and can cause oxidative damage to DNA [ 37 ]. In our study, PKCOS exhibited higher T-AOC activity than açai fermentation extracts [ 38 ] but lower than Buddleja scordioides Kunth [ 39 ], higher • DPPH radical scavenging activity in vitro than BHA [ 40 ] and higher • OH radical percentage of inhibition than gallic acid [ 41 ], which may indicate that PKCOS acts as a potential antioxidant agent.…”
Section: Discussionmentioning
confidence: 86%
“…Free radical scavenging activity of the extracts was evaluated by DPPH radical scavenging assay [71]. The determination procedure was described in detail in our previous work [72]. Ascorbic acid (Sigma Aldrich) was used as reference antioxidant.…”
Section: 2-diphenyl-1-picrylhydrazyl (Dpph) Radical Scavenging Assaymentioning
confidence: 99%